Feasibility of health-related quality of life (HRQoL) assessment for cancer patients using electronic patient-reported outcome (ePRO) in daily clinical practice - Mouillet, Guillaume; Falcoz, Antoine; Fritzsch, Joëlle; Almotlak, Hamadi; Jacoulet, Pascale; Pivot, Xavier; Villanueva, Cristian; Mansi, Laura; Kim, Stefano; Curtit, Elsa; Meneveau, Nathalie; Adotevi, Olivier; et al. (Quality of life research, 2021)
Introduction Routine Electronic Monitoring of Health-Related Quality of Life (HRQoL) (REMOQOL) in clinical care with real-time feedback to physicians could help to enhance patient-centered care. We evaluated the feasibility of REMOQOL in the French context in the QOLIBRY study. The primary objective was to assess the patients’ compliance with REMOQOL. Methods The QOLIBRY study was a single-center, prospective study conducted in the University Hospital of Besançon (France). Eligible patients were those treated with systemic therapies for breast, lung or colorectal cancer at any stage. Patients were invited to complete the EORTC QLQ-C30 questionnaire and cancer-site-specific modules before each visit on tablets and/or computers in the hospital or at home. During the consultation, physicians had real-time access to visual summaries of HRQoL scores. Compliance was assessed as adequate if at least 66% of HRQoL assessments were completed during the 4 months of follow-up. Results Between March 2016 and October 2018, 177 patients were included in the QOLIBRY study. Median age was 64 years (IQR 54–71). The proportion of patients with an adequate compliance rate was 95.5% ( n = 63) in the breast cancer cohort, 98.2% ( n = 55) in the colorectal cancer cohort, and 90.9% ( n = 50) in the lung cancer cohort. The physicians checked the HRQoL results in 73.1% of visits and prescribed supportive care and adapted patient management in 8.3% and 5.2% of visits, respectively. Conclusion & perspectives The results of QOLIBRY study suggest that REMOQOL is feasible in the French context. However, information about HRQoL monitoring, training of the physicians in the use of the software, and recommendations for using HRQoL results to guide care are essential and must be improved.